Defining patterns in the implementation of digital marketing of innovative products in order to improve the level of financial results - Tataryntseva, Yuliia; Kryvobok, Ruslan (Technology center PC, 2024)
The object of research is digital marketing of innovative products. The problem addressed in the study was the need to define digital marketing tools for the promotion of innovative products in order to increase the financial results of enterprises. The specificity of digital marketing of innovative products, which have their own specificity, has been clarified, including the need to explain the benefits of new technologies to consumers. The results of the research revealed that the study of the target audience using analytical tools allows better optimization of marketing campaigns. It has been proven that the substantiation of the expenditure budget based on the method "from the achievement of goals" provides effective use of marketing resources and flexibility in case of changes in market conditions. The advantages of this budgeting method have been revealed, which makes it possible to clearly define marketing goals and direct resources to achieve them. This ensures optimal use of marketing resources. On the basis of regression analysis, the influence of expenses on various digital marketing tools on the total income of the enterprise was determined. Verification of the guidelines included an assessment of the impact of various digital marketing tools on total revenue. Based on the regression analysis, it was established that the costs of setting up a website and search advertising, advertising in social networks and email marketing showed a significant positive impact on the total income of the enterprise. However, spending on content marketing revealed a negative effect. The identified dependences made it possible to accurately assess the impact of each marketing tool on the total revenue of the enterprise, which is critical for effective planning of marketing campaigns and cost optimization.
Keywords: digital marketing; innovative products; advertising effectiveness; product promotion; marketing campaign; financial justification